EVALUATION OF THE GROWTH OF TILAPIA AND AFRICAN CATFISH IN PONDS FERTILIZED WITH POULTRY MANURE AND COW DUNG - OJUWONI, A. A; AKINWOLE, A. O.; FATUROTI , E. O. (Nigerian Journal of Fisheries, 2020)
A thirteen-week growth evaluation study was carried out to evaluate the effect of pond fertilization with poultry manure and cow dung on the growth of Clarias gariepinus and Oreochromis niloticus fingerlings. This study, therefore, evaluates the use of poultry manure and cow dung in the fertilization of ponds for the culture of Oreochromis niloticus and Clarias gariepinus fingerlings. A control experiment with no manure was set-up with both fish fed twice a day on normal 35.4% crude protein feed. Fish raised in ponds with fertilized poultry manure (Tank A and Tank B) had the best growth performance in terms of weight gain and specific growth rate compared with fish fed on cow dung (Tank C and Tank D) and the control experiment (Tank E and Tank F). There was a significant difference (p< 0.05) in the total weight gain and the specific growth rate of the fish in all the treatments. Clarias gariepinus performed better than Oreochromis niloticus in both treatments. Considering the growth performance of total weight gain, mean weight gain and specific growth rate in the treatment tanks, Tank A and Tank B, poultry manure was found most profitable and cheapest to use for pond fertilization.